Peran Usaha Kecil Menengah (Ukm) Dalam Pengembangan Ekonomi Masyarakat - Fadilah, Gina Nur; Saeful Amin, Dang Eif; Dewi, Ratna (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2023)
The economic and social conditions of the people of Garut Regency are still concerning. One solution to this is to empower community participation through SMEs, UKM in Kersamanah Village are engaged in making cassava chips. This effort helps as the community moves, develops to become more empowered. The purpose of this study was to determine the cassava chip business development program, the implementation process, and the results of community development by cassava chip entrepreneurs in Calingcing village in improving the community's economy. The method used in this study is a qualitative method, because the main purpose of this research is to explain, analyze, describe and classify living conditions. Based on the results of the study, it shows that small and medium enterprises have a very important and strategic role in domestic economic development, including in the recruitment of workers due to the large number of jobs, the unemployment rate will decrease. The results obtained by the local community include an increase in the economy from before.